2015
DOI: 10.1002/acp.3181
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Evaluation and Evidence Integration in Legal Decision‐Making: Order of Evidence Presentation as a Moderator of Context Effects

Abstract: Legal decision-making studies often demonstrate context effects: People's initial beliefs about a suspect's guilt influence their evaluation of subsequent evidence. We examine three potential moderators of these context effects: Order of evidence presentation, ability to ruminate, and valence of the initial belief (innocence or guilt). College students (n = 382) were presented with DNA evidence (incriminating or exonerating) and an ambiguous alibi in one of two orders (or just the alibi), and then evaluated ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 24 publications
7
22
3
Order By: Relevance
“…Moreover, they concluded that the piece of evidence that is presented last does not retroactively influence evaluations of the evidence that was presented earlier. However, similarly to the finding by Price and Dahl (2014), Charman et al (2016) also found that the piece of evidence that was presented last had a greater impact on the overall assessment of guilt. Charman et al (2016) therefore suggested that evidence evaluation is likely to be influenced by an existing belief, whereas the evidence integration is likely to be influenced by a recency effect.…”
Section: Order Effectssupporting
confidence: 66%
See 2 more Smart Citations
“…Moreover, they concluded that the piece of evidence that is presented last does not retroactively influence evaluations of the evidence that was presented earlier. However, similarly to the finding by Price and Dahl (2014), Charman et al (2016) also found that the piece of evidence that was presented last had a greater impact on the overall assessment of guilt. Charman et al (2016) therefore suggested that evidence evaluation is likely to be influenced by an existing belief, whereas the evidence integration is likely to be influenced by a recency effect.…”
Section: Order Effectssupporting
confidence: 66%
“…However, similarly to the finding by Price and Dahl (2014), Charman et al (2016) also found that the piece of evidence that was presented last had a greater impact on the overall assessment of guilt. Charman et al (2016) therefore suggested that evidence evaluation is likely to be influenced by an existing belief, whereas the evidence integration is likely to be influenced by a recency effect. As these studies on order effects looked only at the presentation of two pieces of evidence, the effect of alternating the presentation of incriminating and exonerating evidence remains unexamined.…”
Section: Order Effectssupporting
confidence: 66%
See 1 more Smart Citation
“…Similarly, police trainees had greater faith in incriminating evidence that confirmed their expectations regarding a suspect's guilt (Marksteiner et al, 2011). This phenomenon is also supported by evidence of a primacy effect in evidence evaluation, such that the first piece of evidence, which presumably sets expectations, influences the evaluation of subsequent pieces (Charman et al, 2017; Charman, Carbone, Kekessie, & Villalba, 2016). While these and other studies have established that cognitive biases affect evidence evaluation in forensic contexts (see Ask et al, 2008; Charman et al, 2016; Ruva & Guenther, 2017), there is currently limited research on the extent to which evidence direction (incriminating versus exonerating) moderates the influence of ethnicity on alibi credibility assessments.…”
Section: Introductionmentioning
confidence: 85%
“…In terms of forensic evidence, some of the types of evidence that are presented in the PIM manual as compelling forms of evidence (Carr, 2015, p. 188)such as tire impressions, tool marks, and blood spatter analysisare, in fact, unsupported by scientific research (National Research Council, 2009; see also Cediel & Bergman, 2012). Additionally, forensic psychology research suggests that case information has the power to taint the interpretation and integration of forensic evidence (e.g., Charman, 2013;Charman, Carbone, Kekessie, & Villalba, 2016;Dror, Charlton, & Péron, 2006;Kassin, Bogart, & Kerner, 2012;Kassin, Dror, & Kukucka, 2013).…”
Section: Issue 2: Presenting Mischaracterized Evidencementioning
confidence: 99%